B – Flow assessment of femoral artery as predictor of coronary artery disease in patients evaluated for chest pain by radionuclide myocardial perfusion scintigraphy - Avramovski, Petar; Avramovska, Maja; Servini, Zaklina; Nikleski, Zorica; Veljanovska, Keti; Mihajlova, Snezana; Sotiroski, Kosta; Sikole, Aleksandar (World Journal of Nuclear Medicine, 2019)
In the evaluation of patients with suspected coronary artery disease (CAD), the presence of the superficial femoral artery (SFA) plaque is more informative than a carotid plaque and at least as informative as coronary plaque in the identification of coronary death individuals. In 60 patients with chest pain with a normal electrocardiogram, B-flow ultrasound estimation of SFA plaque and radionuclide myocardial perfusion scintigraphy (MPS) estimation for CAD was performed. We found significant positive correlations between age and SFA plaque score (PS) (P = 0.0084), myocardial ischemia in rest and SFA PS (P < 0.0001), and between transient ischemic dilation (TID) and SFA PS (P = 0.0069), too. The TID correlates only with myocardial ischemia in rest (P = 0.0022) and SFA PS (P = 0.0069). The results we got by the receiver operating characteristics (ROC) curve analysis with TID/without TID were the area under curve (0.704, P = 0.0038). The multiple regression analysis showed standardized coefficient β coefficients for SFA PS and TID (3.4577 and 1.9903, P < 0.001 and P = 0.0021), respectively. By proven correlative relationship of SFA atherosclerotic plaques and CAD, we can use B-flow as a screening method for triage of patients with chest pain before being sent to the assessment of coronary circulation with radionuclide MPS.
Keywords: Atherosclerotic plaque; B-flow; coronary artery disease; myocardial perfusion scintigraphy; superficial femoral artery